Searches for continuous gravitational waves from nine young supernova remnants - Dominguez, Alfredo Eduardo (2015)
science data run. The targets were nine young supernova remnants not associated with pulsars; eight of the remnants are associated with non-pulsing suspected neutron stars. One target’s parameters are uncertain enough to warrant two searches, for a total of ten. Each search covered a broad band of frequencies and first and second frequency derivatives for a fixed sky direction. The searches coherently integrated data from the two LIGO interferometers over time spans from 5.3–25.3 days using the matched-filtering F-statistic. We found no credible gravitational-wave signals. We set 95% confidence upper limits as strong (low) as 4 × 10−25 on intrinsic strain, 2 × 10−7 on fiducial ellipticity, and 4 × 10−5 on r-mode amplitude. These beat the indirect limits from energy conservation and are within the range of theoretical predictions for neutron-star ellipticities and r-mode amplitudes.